AN ANALYSIS OF FARIS' EMOTIONS IN THE FILM 'QALB AL-ASAD': A PSYCHOLOGICAL LITERARY STUDY OF DAVID KRECH - Ali, Putri Mas Maulya Hasanah Ramadhan; Anas, Muhammad Irfan (Journal of Arabic Language and Literature (ALLAIS), 2024)
This study aims to classify and analyze the emotions experienced by the main character “Faris” in the film Qalb Al-Asad (Heart of a Lion) using David Krech’s classification of emotions. The theoretical framework is based on Krech’s theory, which categorizes emotions into four types: (1) basic emotions, (2) emotions related to sensory stimulation, (3) emotions related to self-evaluation, and (4) emotions related to others. The research employs a qualitative descriptive method. The primary data consists of verbal and non-verbal expressions illustrating the emotional classifications of Faris' character. The data source is the film Qalb Al-Asad, directed by Hossam Mousa. Data collection techniques include listening, observing, classifying, and describing emotional expressions based on Krech’s theory. Content analysis is used to identify, classify, and analyze scenes in the film to understand the emotions conveyed through both verbal and non-verbal expressions. The findings reveal 38 instances of emotional classifications for the main character Faris in the film Qalb Al-Asad, categorized as follows: 21 instances of basic emotions (happiness, anger, fear, sadness), 2 instances of emotions related to sensory stimulation (pain, enjoyment), 9 instances of emotions related to self-evaluation (success, pride, guilt, regret), and 6 instances of emotions related to others (love, hatred).